2019
DOI: 10.3390/app9030383
|View full text |Cite
|
Sign up to set email alerts
|

Study on Optical Properties and Internal Quantum Efficiency Measurement of GaN-based Green LEDs

Abstract: In this paper, the optical properties of GaN-based green light emitting diode (LED) are investigated and the internal quantum efficiency (IQE) values are measured by temperature dependent photoluminescence (TDPL) and power dependent photoluminescence (PDPL) methods. The "S-shaped” shift of peak wavelength measured at different temperature disappears gradually and the spectra broadening can be observed with increasing excitation power. The IQE calculation results of TDPL, which use the integrated intensity meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In the 296 K mapping, the maximum intensity is located in the middle of the pixel and decreases while approaching the edges. When the temperature is lowered, the emitted intensity becomes higher, as expected from the suppression of non-radiative recombinations in the bulk and the surface [14], [15]. This increased emission of light at the edges of the MESA gives the impression that the MESA size is increasing while lowering temperature (in figure 2, the emission can be compared with the white dashed square which represents the emitted light at 296 K).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In the 296 K mapping, the maximum intensity is located in the middle of the pixel and decreases while approaching the edges. When the temperature is lowered, the emitted intensity becomes higher, as expected from the suppression of non-radiative recombinations in the bulk and the surface [14], [15]. This increased emission of light at the edges of the MESA gives the impression that the MESA size is increasing while lowering temperature (in figure 2, the emission can be compared with the white dashed square which represents the emitted light at 296 K).…”
Section: Resultsmentioning
confidence: 90%
“…We conducted the CL characterization on another 6×6 µm² pixel in order to check the repeatability (Figure 8). Since the CL intensity I(T) is maximum at 30 K, we calculated a map representing the emission efficiency using the ratio [14] I(296 K)/I (30 K). This calculation was carried out after an alignment of the images realized at 296 K and 30 K (Figure 8c).…”
Section: Figure 7 Integrated CL Intensity Mappings At Different Temperatures For 36×36 µM² and 56×56 µM² Pixelsmentioning
confidence: 99%
“…The strength of electron–phonon interaction can be described by Huang–Rhys factor, [ 19 ] which can be approximated by the intensity ratio of first‐order phonon replica to zero‐phonon line at low temperature. [ 20 ] The value for GaN‐based materials obtained from experimental data [ 21 ] is ≈10 −1 –10 −2 , implying that vibronic coupling is considerably weak. It can be inferred that multiphoton process whose probability is smaller than observed EQE by several orders of magnitude is rather rare to occur and cannot sustain appreciable emission.…”
Section: Scientific Challenges and Possible Solutionsmentioning
confidence: 99%
“…The light source used in the PL experiment is a 405 nm solid-state laser, the output power of which is decreased to 1 mW to eliminate additional thermal effect, and the spot measures about 55 μm in radius. 23) Figure 1 shows the PL intensity, V OC , and I SC of the two LED samples measured under different bias and temperature conditions. Even though the shapes of these data points are different, it can be observed that the PL intensity and V OC under OC conditions have a similar trend with temperature, while the PL intensity and I SC under SC conditions change contrariwise with temperature, namely the decrease of PL intensity is accompanied by the increase of I SC .…”
mentioning
confidence: 99%